Analisis Strategi Bauran Pemasaran 7p pada UMKM Labuqu di Desa Bulontala Timur, Provinsi Gorontalo - Selviawati Herman; Ria Indriani; Asda Rauf (Yayasan Literasi Sains Indonesia, 2026)
Labuqu MSME is a food-processing enterprise based on organic butternut squash (Cucurbita moschata) located in East Bulontala Village, Bone Bolango Regency, Gorontalo Province. This study aimed to analyze the implementation of the 7P marketing mix, consisting of product, price, place, promotion, people, process, and physical evidence, as well as to formulate marketing strategies based on SWOT analysis. A qualitative descriptive approach was employed, supported by in-depth interviews, Focus Group Discussions (FGDs), and observations. Data were analyzed using the IFES, EFES, IE, and SWOT matrices. The findings indicate that the overall implementation of the 7P marketing mix has been fairly effective, with the main strengths being product diversification based on locally sourced functional raw materials and affordable pricing. However, the place and people dimensions remain weaknesses that require improvement, particularly in terms of limited accessibility to the business location and team coordination. The results of the SWOT analysis show that Labuqu's marketing strategy is positioned in Quadrant I, indicating that the enterprise possesses stronger internal strengths and greater external opportunities than its weaknesses and threats. Under these conditions, an aggressive strategy (Growth-Oriented Strategy) is recommended to support business growth and development.